Pädagogische Wissenschaft in der DDR : Ideologieproduktion, Systemreflexion und Erziehungsforschung. Studien zu einem vernachlässigten Thema der Disziplingeschichte deutscher Pädagogik - Tenorth, Heinz-Elmar 1944- (Bildungsgeschichte. Forschung - Akzente - Perspektiven, 2022)
With their analyses, the Berlin historians of education provide for the first time a historiographically well-founded and systematically grounded history of the development and status of scientific pedagogy in the GDR. It is no longer interpreted solely in ideology-political and critical terms as an auxiliary of SED educational policy, but is comprehensively analyzed in its own practice as a system of different forms of knowledge. As a scientific pedagogy, it developed from 1945 to 1989 in the conflictual field between science and politics, pedagogical practice and educational research, central institutions and individual work into a discipline of its own shape, in the process increasingly also according to its self-understanding a researching discipline in a difficult and highly politicized context